Prácticas sociales de paz en Colombia: el caso de la Confluencia de Mujeres para la Acción Pública - Sandra Julie Solano-Nivia; Nasli Giomara Farfán-Pérez; Julio Jaime-Salas (Revista Crítica de Ciências Sociais, 2022)
This article, derived from research, aims to analyze the social peace practices of the national process of Confluencia de Mujeres para La Acción Pública – CMAP [confluence of women for public action] of 2009-2019, as an expression of the social movement for peace in Colombia. Among the most important conclusions are the opportunity to identify that the social practices of peace of the CMAP become evident in the feminist collective action, being symbolic as political power and the subaltern memories as constructions of knowledge. In turn, the contribution of the social movement in Colombia is recognized, characterized by producing peace practices, while it has been a movement in defense of life and territories.